2003
DOI: 10.1074/jbc.m208857200
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor-β1 Mutations in Camurati-Engelmann Disease Lead to Increased Signaling by Altering either Activation or Secretion of the Mutant Protein

Abstract: Transforming growth factor-␤1 (TGF-␤1) is secreted as a latent precursor, consisting of a homodimer of the latency-associated peptide and the mature peptide. TGF␤-1 can only exert its many functions after going from this latent to an active state, in which the binding site of the mature peptide for its receptor is no longer shielded by the latency-associated peptide. We and others reported that mutations in TGFB1 cause CamuratiEngelmann disease, a rare bone disorder. Until now, seven mutations have been publis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
86
0
6

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 109 publications
(92 citation statements)
references
References 38 publications
0
86
0
6
Order By: Relevance
“…It is intriguing that domain-specific germline mutations of TGFB1 cause Camurati-Engelmann disease (CED, OMIM #131300) (Kinoshita et al 2000) associated with marfanoid habitus, despite the absence of connective tissue fragility. TGFB1 mutations in CED were shown to cause increased TGFb signaling (Janssens et al 2003). These findings suggest that abnormal TGFb signaling could be responsible for the skeletal features of MFS.…”
Section: Germline Tgfbr Mutations and Connective Tissue Disordersmentioning
confidence: 79%
“…It is intriguing that domain-specific germline mutations of TGFB1 cause Camurati-Engelmann disease (CED, OMIM #131300) (Kinoshita et al 2000) associated with marfanoid habitus, despite the absence of connective tissue fragility. TGFB1 mutations in CED were shown to cause increased TGFb signaling (Janssens et al 2003). These findings suggest that abnormal TGFb signaling could be responsible for the skeletal features of MFS.…”
Section: Germline Tgfbr Mutations and Connective Tissue Disordersmentioning
confidence: 79%
“…These molecules can also form a larger covalent complex with a latent TGF-␤-binding protein (LTBP). Activation of TGF␤1, which occurs outside the cell, can occur as the result of low pH or proteolytic activity and results in the release of the active TGF␤1 dimer from the LAP and other inhibitory molecules so that it can now directly interact with the TGF␤1 receptors (Janssens et al 2003). Functional studies have shown that CED-causing mutations all act to increase SMAD-dependent TGF␤1 signaling, but by different mechanisms.…”
Section: Genetics Of Osteoporosis Genes and Development 2497mentioning
confidence: 99%
“…Calvarial and pelvic bone thickening are also common (Janssens et al 2006). CED is caused by TGFB1 missense mutations in the LAP region or signal peptide that destabilize the disulfide binding needed for homodimerization of latent TGF-b1, resulting in increased TGF-b signaling through either premature activation or intracellular retention of the protein and intracrine signal transmission Janssens et al 2003Janssens et al , 2006. Clinical manifestations do not include fibrosis or aneurysm, and no evidence for increased TGF-b signaling has been described in the aortic wall or other tissues, suggesting that these mutations have tissue-specific effects on TGF-b activity.…”
Section: Gain Of Bone Mass In Camurati -Engelmann Diseasementioning
confidence: 99%